Ice mass change and its feedback on solid earth dynamics in the Antarctic peninsula - Samrat, NH (2020)
Rapid regional climate warming in the Antarctic Peninsula (AP) has led to several major ice shelves retreating, and eventually collapsing, since the 1970s. In response, feeding glaciers have exhibited rapid acceleration and thinning, contributing to sea-level rise. This ice mass unloading induces a solid Earth response, which can be measured by geodetic observations. Observed rates of three-dimensional solid Earth deformations contain contributions due to both present and past ice mass variations (i.e. since Last Glacial Maximum, LGM) and horizontal plate tectonics. The solid Earth viscoelastic adjustments due to ice-ocean loading changes are known as Glacial Isostatic Adjustment (GIA). Accurate knowledge of GIA is essential for correcting gravity-based estimates of present-day ice-mass change. Observing solid Earth deformation caused by present-day ice mass change can be used to constrain the GIA response by inferring the Earth's viscoelastic properties. A few studies based on seismic or geodetic datasets have inferred Earth's rheological properties in the AP but the results are not yet conclusive. This thesis seeks to improve understanding of the solid Earth rheology in the AP by using spatiotemporally extended, three-dimensional geodetic observations and viscoelastic modeling. GPS observations up to 2018 are used to constrain the Earth rheology in the region around the former Larsen A and B ice shelves. I make use of interferometric synthetic aperture radar (InSAR) observations to further understand the ice mass change and solid Earth rheology in the northern Antarctic Peninsula (NAP), the first such application of InSAR in Antarctica. Finally, I extend the study region further south, to the northern Marguerite Bay (NMB) region, to determine ice mass change over 2002-2018 and explain non-linear deformation observed in GPS records using viscoelastic modeling. Previous work has shown that GPS measurements of bedrock uplift in the NAP can only be explained by a viscoelastic response to post-2002 ice surface ...